Cementless and cemented total knee arthroplasty in patients younger than fifty five years. Which is better? - Kim, Young-Hoo (Springer Berlin Heidelberg, 2014)
PURPOSE: The purpose of this prospective, randomised study was to evaluate long-term clinical results, radiographic findings, complications and revision and survivorship rates in patients <55 years at a minimum of 16 years after undergoing bilateral, sequential, simultaneous, cemented and cementless total knee arthroplasties (TKAs) in the same patients. METHODS: Bilateral, sequential, simultaneous TKAs were performed in 80 patients (160 knees). There were 63 women and 17 men with a mean age of 54.3 years (range 49–55), who received a cementless prosthesis in one knee and a cemented prosthesis in the other. The mean follow-up was 16.6 years (range 16–17). RESULTS: At final review, the mean Knee Society (KS) knee scores (95.8 versus 96.9), Western Ontario and McMaster Universities (WOMAC) osteoarthritis (OA) index (25.4 versus 25.9), range of motion (ROM) (125°versus 128°), patient satisfaction (8.1 versus 8.3) and radiological results were similar in both groups. Femoral component survival rate was 100 % in both groups at 17 years; at 17 years, the cemented tibial component survival rate was 100 % and the cementless tibial component 98.7 %. No osteolysis was identified in either group. CONCLUSION: Long-term results of both cementless and cemented TKAs were encouraging in patients with OA who were <55 years. However, we found no evidence to prove the superiority of cementless over cemented TKAs.